Spectroscopic Investigation and Synthesis of N-Ethyl-5-Tolyloxymethyl Triazole Derivatives - Ahmed, Shakeel; Murad, Shiza; Munir, Iqra; Sheikh, Samina; Ahmad, Qurat-ul-Ain; Shahid, Namal; Rizvi, Syed Moman Ali; Shahid, Abbas (Indus Journal of Bioscience Research, 2025)
High-nitrogen heterocycles' synthesis has attracted much interest because of their wide applicability in many different sectors. As a significant class of organic compounds, triazoles and their fused derivatives have emerged among these. A new triazole derivative, 4-ethyl-3-ethylthio-5-(p-tolyloxymethyl)-4H-1, 2, 4-triazole, is the subject of this work on synthesis and spectrum characterization. Ethyl 2-p-tolyloxy acetate is synthesized by reacting 3, 4-dimethoxyphenylacetic acid with ethanol under concentrated H2SO4, starting the process. The ester product is subsequently transformed into 2-p-tolyloxyacetohydrazide, which is further reacted with ethyl isothiocyanate to produce 2-p-tolyloxythiosemicarbazide. Cyclizing 275 in an alkaline media generates 4-ethyl-5-(p-tolyloxymethyl)-4H-1, 2, 4-triazole-3-thiol. 276 interacts with several alkyl halides in the last stage to create N-ethyl-3, 5-substituted derivatives (278a-h). Infrared (IR), nuclear magnetic resonance (NMR), electron ionization mass spectrometry (EI-MS), and high-resolution electron ionization mass spectrometry (HR-EI-MS) were used to characterize each chemical. This work adds to the expanding area of nitrogen-rich heterocycles by providing fresh triazole derivatives with possible uses in industrial and medical chemistry.